Contribuições do desenho geométrico no ensino de geometria plana no ensino médio: uma proposta utilizando o GeoGebra como ferramenta pedagógica - Almeida, Paulo Loreço Cruz de (2023)
Geometric construction practices complement artifacts that underpin and consolidate geometric knowledge. However, there are signs of a lack of prestige in the trajectory of the discipline in national curricula, which has led to a gap in the performance of basic education students in relation to geometry. Currently, with technological advances, the use of software in pedagogical practices is increasingly present, and the development of dynamic geometry software makes its application in geometry classes relevant. Thus, this study was developed with the aim of analyzing the contributions of geometric drawing to the learning of plane geometry in high school. Therefore, a didactic sequence was proposed for the study of geometric constructions in which the GeoGebra software was used as a pedagogical tool, applying activities and questionnaires that promoted reflections and pointed out contributions to the discipline of plane geometry. It was observed in the results that these construction practices, in fact, potentiate the study of geometry, effectively contributing to the development of students' logical reasoning, making them able to deduce, conjecture, and justify results with valid arguments, and understand flat figures as abstract objects